Angular Dependence of the Magnetic Properties of Permalloy and Nickel Nanowires as a Function of Their Diameters - Escrig-Murua, J; Tejo-Lazo, F (Institute of Physics Publishing, 2018)
In this paper we have compared the angular dependence of the magnetic properties of permalloy (Ni80Fe20) and nickel nanowires by means of micromagnetic simulations. For each material we have chosen two diameters, 40 and 100 nm. Permalloy nanowires with smaller diameters (d=40 nm) exhibit greater coercivity than nickel nanowires, regardless of the angle at which the external magnetic field is applied. In addition, both Py and Ni nanowires exhibit the same remanence values. However, the nanowires of larger diameters (d=100 nm) exhibit a more complex behavior, noting that for small angles, nickel nanowires are those that now exhibit a greater coercivity in comparison to those of permalloy. The magnetization reversal modes vary as a function of the angle at which the external field is applied. When the field is applied parallel to the wire axis, it reverts through nucleation and propagation of domain walls, whereas when the field is applied perpendicular to the axis, it reverts by a pseudo-coherent rotation. These results may provide a guide to control the magnetic properties of nanowires for use in potential applications. © 2018 IOP Publishing Ltd.